Free Circulation of Information and Online Intermediaries – Replacing One “Value Gap” with Another - Valentina Moscon (IIC - International Review of Intellectual Property and Competition Law, 2020)
The role of online intermediaries in allowing third parties to perform legal as well as illegal activities and the growing economic power of such intermediaries are profoundly challenging the legal framework established 20~years ago with the European Union e-Commerce Directive. European courts first, and legislatures more recently, have taken a position regarding the need for further regulation of online intermediaries. The new liability rules for copyright infringement are just an example of a more general tendency to charge intermediaries with responsibility. This tendency goes beyond the realm of intellectual property and includes consumer law, antitrust and competition law. The forthcoming EU~Digital Services Act aims to revise the regulation of online intermediaries by means of new rules framing the responsibilities of digital services and online platforms' market behaviour.In this context there is no doubt that the current scenario requires modern rules. However, it is licit to ask whether and how European institutions are considering the collateral effects of the above-mentioned tendency. It is also not clear how the basic principles underpinning the e-Commerce Directive – and, in particular, freedom of expression – will be assured in a new legal framework where online intermediaries may not enjoy the safe harbours originally laid down in the e-Commerce Directive.
Keywords: 340; Online intermediaries; EU e-Commerce Directive; EU~Digital Services Act; Freedom of expression; Safe harbors; Platform self-regulation